Secondary copper slag geopolymer stabilized macadam base material and preparation method thereof
By preparing secondary copper slag earth polymer to stabilize gravel base materials, and using raw materials such as copper slag, the problem of low copper slag disposal utilization rate is solved, and the resource utilization and environmental protection of copper slag is achieved, with high strength, low cost and excellent anti-freeze properties.
Patent Information
- Application Number
- CN202510035778.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
The existing technology is difficult to effectively utilize copper slag, resulting in a low utilization rate of copper slag disposal and utilization, resulting in environmental pollution and waste of resources.
By preparing a secondary copper slag polyester stabilized gravel base material, using copper slag, gravel material, nano C-S-H, alkali trigger, shrinkage agent and straw ash and other raw materials, it is mechanically stirred and compacted to form a base material with high strength, low shrinkage and excellent frozen resistance.
It has realized the resource utilization of copper slag, reduced environmental pollution and carbon emissions, and has the advantages of low cost, convenient construction, high strength and excellent frost resistance. It is suitable for base materials for highway projects.
Smart Images

Figure BDA0005235501760000071 
Figure BDA0005235501760000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of comprehensive utilization of solid waste materials, and in particular to a secondary copper slag geopolymer-stabilized crushed stone base material and a preparation method thereof. Background Art
[0002] my country is the world's third largest copper producer and the largest copper consumer. Although my country is rich in copper resources, most of them are poor ores, which are difficult and costly to beneficiate, and a large amount of copper slag is produced during the smelting process. According to the "China Mineral Resources Report (2020)" released by the Ministry of Natural Resources, my country's refined copper output was 9.029 million tons in 2018 and increased to 9.784 million tons in 2019. For every ton of refined copper produced, about 2 to 3 tons of copper slag are produced, so my country produces about 20 to 30 million tons of copper slag each year.
[0003] At present, the treatment of copper slag is mainly concentrated in the fields of valuable metal recovery, building materials and catalysis. Although these fields can dissolve some copper slag, the disposal and utilization rate of copper slag in my country is still low, resulting in a large amount of copper slag being difficult to effectively utilize. The disorderly stacking of copper slag not only encroaches on arable land resources, but also causes serious environmental pollution. How to achieve the resource utilization and harmless treatment of copper slag through technical means is a difficult problem that needs to be solved urgently. With the rapid development of my country's highway industry, cement, as the main material for highway engineering, consumes a huge amount. The application of copper slag in highway engineering can promote the resource utilization of copper slag solid waste in highway construction. Using copper slag for cement-stabilized gravel base can not only alleviate environmental problems, but also save cement and reduce carbon emissions. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention provides a secondary copper slag geopolymer-stabilized gravel base material and a preparation method thereof. The material has the advantages of low shrinkage, strong stability, low cost, high strength and convenient construction, and can effectively reduce environmental pollution and reduce carbon emissions.
[0005] To achieve the above objectives, the present invention is implemented through the following technical solutions:
[0006] A secondary copper slag geopolymer stabilized crushed stone base material, the base material is made of the following raw materials in parts by weight: 10-15 parts of copper slag, 29-43 parts of crushed stone, 4-6 parts of water, 20-30 parts of straw ash, 5-8 parts of nano CSH, 1-2 parts of alkali activator, and 0.12-0.18 parts of shrinkage reducer
[0007] Preferably, the copper slag has a particle size of ≤12 μm and a specific surface area of greater than 400 m 2 / kg, and the total content of CaO, SiO2, Al2O3, Fe2O3 and MgO compounds in the copper slag is ≥90%, and the loss on ignition is ≤2%.
[0008] Preferably, the crushed stones are all basalt aggregates, and the grading of the crushed stones should meet the following requirements: the mass ratio of crushed stone with a particle size of 0-5 mm: crushed stone with a particle size of 5-10 mm: crushed stone with a particle size of 10-15 mm: crushed stone with a particle size of 15-20 mm is 22-34:16-24:15-28:11-23; and the crushing value of the crushed stone is ≤20%, the needle-like content is ≤26%, and the content below 0.075 mm is ≤5%.
[0009] Preferably, the straw ash particle size is ≤15 μm and the specific surface area is greater than 250 m 2 / kg, the passing rate of 0.3mm sieve hole is ≥90%, the passing rate of 0.075mm sieve hole is ≥70%; and the total content of SiO2, Al2O3, CaO and MgO compounds in straw ash is >90%, and the loss on ignition is ≤10%.
[0010] Preferably, the nano-CSH is nano-calcium silicate hydrate with polycarboxylic acid as a dispersant.
[0011] Preferably, the alkaline activator is carbide slag.
[0012] Preferably, the shrinkage reducing agent is a silane coupling agent.
[0013] The preparation method of the base material comprises the following steps:
[0014] (1) Accurately weigh all raw materials, pour the crushed stone into the mixing equipment, and add water to wet it so that the crushed stone can fully absorb water;
[0015] (2) adding copper slag, straw ash and nano-CSH to the wetted gravel, then adding alkali activator and shrinkage reducing agent, and stirring evenly with a mechanical stirrer or mixer until the raw materials are fully mixed to obtain a mixture for use;
[0016] (3) The mixture is laid as the base material of the road according to the design required thickness and compacted. Subsequently, a film is covered on the surface of the material for maintenance. The maintenance method is to regularly sprinkle water to keep it moist, promote solidification, and ensure the formation of a stable copper slag road base.
[0017] Preferably, the compaction degree of the compaction treatment in step (3) needs to reach or exceed 98%, using a 20-ton roller for static compaction 2 to 3 times, followed by 3 to 4 times of vibration compaction with a 26-ton roller, and finally final compaction with a tire roller.
[0018] Preferably, the curing time in step (3) is not less than 7 days.
[0019] The present invention provides a secondary copper slag geopolymer-stabilized crushed stone base material and a preparation method thereof, which has the following advantages over the prior art:
[0020] (1) The present invention uses copper slag with a particle size of less than 12 μm, which is mixed with crushed stone, nano CSH, alkali activator, shrinkage reducer, straw ash and water to further stimulate the volcanic ash activity of amorphous SiO2 and Al2O3 in the copper slag and straw ash, thereby improving the strength of the mixture;
[0021] (2) The present invention is of great significance for the solid waste resource utilization of waste copper slag, reducing carbon emissions and protecting the environment, and opens up a new way for the recycling of copper slag;
[0022] (3) The base material of the present invention exhibits excellent strength performance and can fully activate the active components in the copper slag. Its 7d unconfined compressive strength exceeds 7.41MPa, its 90d indirect tensile strength is not less than 0.8MPa, and its flexural tensile strength reaches more than 2MPa. These strength indicators all exceed the corresponding values of ordinary cement-stabilized crushed stone and can meet the requirements of the base and subbase of traffic highway pavement;
[0023] (4) The base material of the present invention has excellent shrinkage performance and anti-freezing performance. At the age of 28 days, the shrinkage of the mixture tends to be stable and does not exceed 0.5 mm. After 7 freeze-thaw cycles, the strength loss of the mixture at the age of 28 days is less than 10%, and the mass loss is only 3.1%. These performance indicators meet the requirements of relevant specifications;
[0024] (5) The copper slag road base material of the present invention has a low cost. Compared with ordinary cement stabilized stone, the cost of using copper slag is reduced by more than 30%. Among them, the materials such as copper slag, crushed stone, and straw ash themselves have no cost, and the cost generated is mainly the transportation cost. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The following copper slag comes from Jinchang Smelter of Anhui Tongling Nonferrous Metals Group Co., Ltd. The total content of CaO, SiO2, Al2O3, Fe2O3 and MgO compounds in the copper slag is ≥90%, and the loss on ignition is ≤2%; the crushing value of crushed stone is ≤20%, the needle-like content is ≤26%, and the content below 0.075 mm is ≤5%; the specific surface area of straw ash is greater than 250m 2 / kg, the passing rate of 0.3mm sieve hole is ≥90%, the passing rate of 0.075mm sieve hole is ≥70%; and the total content of SiO2, Al2O3, CaO and MgO compounds in straw ash is >90%, and the loss on ignition is ≤10%.
[0027] Embodiment 1:
[0028] A secondary copper slag geopolymer stabilized crushed stone base material, comprising the following components in parts by weight: 10 parts of copper slag, 29 parts of crushed stone, 0.12 parts of silane coupling agent, 1 part of carbide slag, 4 parts of water, 20 parts of straw ash, and 5 parts of nano CSH;
[0029] The particle size of copper slag is 12μm, the particle size of straw ash is 15μm, and among the crushed stones, the particle size of 0-5mm accounts for 27%, the particle size of 5-10mm accounts for 27%, the particle size of 10-15mm accounts for 36%, and the particle size of 15-20mm accounts for 10%.
[0030] According to the weight fraction of each component in the above formula, copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are weighed respectively, and then copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are added into a mixer for mixing and stirring to obtain a secondary copper slag geopolymer-stabilized crushed stone base material.
[0031] Embodiment 2:
[0032] A method for preparing a secondary copper slag geopolymer-stabilized crushed stone base material, comprising the following components in parts by weight: 12 parts of copper slag, 30 parts of crushed stone, 0.12 parts of silane coupling agent, 1 part of carbide slag, 5 parts of water, 24 parts of straw ash, and 5 parts of nano-CSH;
[0033] The particle size of copper slag is 12μm, the particle size of straw ash is 15μm, and among the crushed stones, the particle size of 0-5mm accounts for 25%, the particle size of 5-10mm accounts for 25%, the particle size of 10-15mm accounts for 40%, and the particle size of 15-20mm accounts for 10%.
[0034] According to the weight fraction of each component in the above formula, copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are weighed respectively, and then copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are added into a mixer for mixing and stirring to obtain a secondary copper slag geopolymer-stabilized crushed stone base material.
[0035] Embodiment 3:
[0036] A preparation method of a secondary copper slag geopolymer-stabilized crushed stone base material comprises the following components in parts by weight: 13 parts of copper slag, 37 parts of crushed stone, 0.12 parts of silane coupling agent, 1 part of carbide slag, 5 parts of water, 26 parts of straw ash, and 6 parts of nano-CSH; the copper slag has a particle size of 10 μm, the straw ash has a particle size of 12 μm, and in the crushed stone, the proportion of crushed stone with a particle size of 0-5 mm is 25%, the proportion of crushed stone with a particle size of 5-10 mm is 30%, the proportion of crushed stone with a particle size of 10-15 mm is 35%, and the proportion of crushed stone with a particle size of 15-20 mm is 10%.
[0037] According to the weight fraction of each component in the above formula, copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are weighed respectively, and then copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are added into a mixer for mixing and stirring to obtain a secondary copper slag geopolymer-stabilized crushed stone base material.
[0038] Embodiment 4:
[0039] A preparation method of a secondary copper slag geopolymer-stabilized crushed stone base material comprises the following components in parts by weight: 14 parts of copper slag, 40 parts of crushed stone, 0.168 parts of silane coupling agent, 2 parts of carbide slag, 5 parts of water, 28 parts of straw ash, and 6 parts of nano-CSH, wherein the copper slag has a particle size of 10 μm, the straw ash has a particle size of 12 μm, and in the crushed stone, the proportion of crushed stone with a particle size of 0-5 mm is 25%, the proportion of crushed stone with a particle size of 5-10 mm is 30%, the proportion of crushed stone with a particle size of 10-15 mm is 35%, and the proportion of crushed stone with a particle size of 15-20 mm is 10%.
[0040] According to the weight fraction of each component in the above formula, copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are weighed respectively, and then copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are added into a mixer for mixing and stirring to obtain a secondary copper slag geopolymer-stabilized crushed stone base material.
[0041] Embodiment 5:
[0042] A preparation method of a secondary copper slag geopolymer-stabilized crushed stone base material comprises the following components in parts by weight: 15 parts of copper slag, 40 parts of crushed stone, 0.168 parts of silane coupling agent, 2 parts of carbide slag, 5 parts of water, 30 parts of straw ash, and 7 parts of nano-CSH; the copper slag has a particle size of 8 μm, the straw ash has a particle size of 9 μm, and in the crushed stone, the proportion of crushed stone with a particle size of 0-5 mm is 20%, the proportion of crushed stone with a particle size of 5-10 mm is 30%, the proportion of crushed stone with a particle size of 10-15 mm is 40%, and the proportion of crushed stone with a particle size of 15-20 mm is 10%.
[0043] According to the weight fraction of each component in the above formula, copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are weighed respectively, and then copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are added into a mixer for mixing and stirring to obtain a secondary copper slag geopolymer-stabilized crushed stone base material.
[0044] Embodiment 6:
[0045] A preparation method of a secondary copper slag geopolymer-stabilized crushed stone base material comprises the following components in parts by weight: 15 parts of copper slag, 40 parts of crushed stone, 0.18 parts of silane coupling agent, 2 parts of carbide slag, 6 parts of water, 30 parts of straw ash, and 7 parts of nano-CSH; the copper slag particle size is 8 μm, the straw ash particle size is 9 μm, the river sand particle size is 0.45 mm, and in the crushed stone, the proportion of crushed stone with a particle size of 0-5 mm is 20%, the proportion of crushed stone with a particle size of 5-10 mm is 30%, the proportion of crushed stone with a particle size of 10-15 mm is 40%, and the proportion of crushed stone with a particle size of 15-20 mm is 10%.
[0046] According to the weight fraction of each component in the above formula, copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are weighed respectively, and then copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are added into a mixer for mixing and stirring to obtain a secondary copper slag geopolymer-stabilized crushed stone base material.
[0047] Comparative Example 1:
[0048] A cement-stabilized crushed stone mixture, comprising the following components in parts by weight: 50 parts of stone, 24 parts of cement, 8 parts of water, and 36 parts of river sand;
[0049] According to the weight fraction of each component in the above formula, stone, cement, river sand and water are weighed respectively, added into a mixer and mixed to obtain a cement-stabilized crushed stone mixture.
[0050] Comparative Example 2:
[0051] A method for preparing a secondary copper slag geopolymer-stabilized crushed stone base material, comprising the following components in parts by weight: 15 parts of copper slag, 40 parts of crushed stone, 0.18 parts of silane coupling agent, 2 parts of carbide slag, 6 parts of water, 30 parts of straw ash, and 8 parts of nano-CSH;
[0052] According to the weight fraction of each component in the above formula, copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are weighed respectively, and then copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are added into a mixer for mixing and stirring to obtain a secondary copper slag geopolymer-stabilized crushed stone base material.
[0053] Comparative Example 3:
[0054] A method for preparing a secondary copper slag geopolymer-stabilized crushed stone base material, comprising the following components in parts by weight: 14 parts of copper slag, 40 parts of crushed stone, 0.168 parts of silane coupling agent, 2 parts of carbide slag, 5 parts of water, 28 parts of straw ash, and nano-CSH;
[0055] According to the weight fraction of each component in the above formula, copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are weighed respectively, and then copper slag, crushed stone, silane coupling agent, carbide slag, water, straw ash and nano-CSH are added into a mixer for mixing and stirring to obtain a secondary copper slag geopolymer-stabilized crushed stone base material.
[0056] Detection:
[0057] The base materials of Examples 1-6 and Comparative Examples 1-3 were tested according to the test methods T0805-1994 and T 0858-2009 in the "Testing Procedure for Inorganic Binder Stabilized Materials for Highway Engineering" (JTG E51-2009) to obtain the 7d unconfined compressive strength, 28d unconfined compressive strength and 28d post-freeze-thaw compressive strength. The test results are shown in Table 1:
[0058] Table 1
[0059]
[0060]
[0061] As can be seen from Table 1, the 7d unconfined compressive strength, 28d unconfined compressive strength and 28d post-freeze-thaw compressive strength of the base materials of Examples 1-6 of the present invention are all relatively high, and can be well used as a road base and subbase. From the post-freeze-thaw strength loss BDR (compressive strength after freeze-thaw / unconfined compressive strength of the control group) data, it can be seen that the road base material prepared using the secondary copper slag geopolymer has good antifreeze performance.
[0062] On the basis of Example 1, the four dosages of copper slag, carbide slag, silane coupling agent and straw ash are controlled to form Comparative Examples 1-3. By comparing Example 1 with Comparative Example 1, it can be seen that the use of secondary copper slag geopolymer as the main cementitious material, supplemented by carbide slag as an activator and silane coupling agent as a shrinkage reducing agent, can significantly improve the strength of the material and reduce cracking, while reducing the dependence on the amount of cement, and alleviating the shrinkage cracking problem of the base material. Compared with Comparative Examples 2 and 3, carbide slag and silane coupling agent KH79 have obvious effects on improving strength and reducing cracking. The secondary copper slag geopolymer stabilized crushed stone base material proposed in the present invention has better compressive strength and frost resistance than the control sample, showing good performance in use.
[0063] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A secondary copper slag geopolymer stabilized gravel base material, characterized by: The base material is made of the following raw materials in parts by weight: 10-15 parts of copper slag, 29-43 parts of crushed stone, 4-6 parts of water, 20-30 parts of straw ash, 5-8 parts of nano CSH, 1-2 parts of alkali activator, and 0.12-0.18 parts of shrinkage reducer.
2. The base material according to claim 1, characterized in that: The copper slag has a particle size of ≤12 μm and a specific surface area of greater than 400 m 2 / kg, and the total content of CaO, SiO2, Al2O3, Fe2O3 and MgO compounds in the copper slag is ≥90%, and the loss on ignition is ≤2%.
3. The base material according to claim 1, characterized in that: The crushed stones are all basalt aggregates, and the grading of the crushed stones should meet the following requirements: the mass ratio of crushed stone with a particle size of 0-5mm: crushed stone with a particle size of 5-10mm: crushed stone with a particle size of 10-15mm: crushed stone with a particle size of 15-20mm is 22-34:16-24:15-28:11-23; and the crushing value of the crushed stone is ≤20%, the needle-like content is ≤26%, and the content below 0.075mm is ≤5%.
4. The base material according to claim 1, characterized in that: The straw ash particle size is ≤15μm and the specific surface area is greater than 250m 2 / kg, the passing rate of 0.3mm sieve hole is ≥90%, the passing rate of 0.075mm sieve hole is ≥70%; and the total content of SiO2, Al2O3, CaO and MgO compounds in straw ash is >90%, and the loss on ignition is ≤10%.
5. The base material according to claim 1, characterized in that: The nano CSH is nano calcium silicate hydrate using polycarboxylic acid as a dispersant.
6. The base material according to claim 1, characterized in that: The alkaline activator is carbide slag.
7. The base material according to claim 1, characterized in that: The shrinkage reducing agent is a silane coupling agent.
8. A method for preparing a base material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) Accurately weigh all raw materials, pour the crushed stone into the mixing equipment, and add water to wet it so that the crushed stone can fully absorb water; (2) adding copper slag, straw ash and nano-CSH to the wetted gravel, then adding alkali activator and shrinkage reducing agent, and stirring evenly with a mechanical stirrer or mixer until the raw materials are fully mixed to obtain a mixture for use; (3) The mixture is laid as the base material of the road according to the design required thickness and compacted. Subsequently, a film is covered on the surface of the material for maintenance. The maintenance method is to regularly sprinkle water to keep it moist, promote solidification, and ensure the formation of a stable copper slag road base.
9. The preparation method according to claim 8, characterized in that: The compaction degree of the compaction treatment in step (3) must reach or exceed 98%, using a 20-ton roller for static compaction 2 to 3 times, followed by a 26-ton roller for vibration compaction 3 to 4 times, and finally a tire roller for final compaction.
10. The preparation method according to claim 8, characterized in that: The curing time in step (3) is not less than 7 days.